Examination of dietary methylmercury exposure in the Casa Pia study of the health effects of dental amalgams in children - Evens, Carina C. (2018)
This study examined methylmercury concentrations in blood of children participating in the Casa Pia Study of the Health Effects of Dental Amalgams in Children over a 1-yr period and related them to their diets in terms of fish and other seafood consumption. One hundred and fifty children between the ages of 8 and 10 yr who were residents of the Casa Pia School System of Lisbon, Portugal, participated. Parents or caregivers completed a food frequency questionnaire designed specifically for this study at baseline. Children provided urinary and blood samples for mercury determinations at baseline and at 1 yr following placement of dental tooth fillings. Mercury levels in fish samples from children’s diets were also obtained. Mercury determinations in urine, blood, and fish were performed using cold vapor atomic fluorescence spectroscopy. The mean value of baseline methylmercury concentrations in blood increased as the report of seafood consumption increased, although not statistically significantly. However, blood methylmercury and total mercury concentrations were significantly lower at 1-yr follow-up than at baseline. Sixty-one percent of parents/ caregivers reported that their children consumed fish on a weekly basis. The fish offered at a sample of the schools contained low levels of methylmercury ( range 13.9–23.6 ng/ g) . Thus, children participating in the Casa Pia dental amalgam study are exposed to low dietary levels of methylmercury by way of fish consumption, and this finding was reflected in the low mean blood methylmercury concentrations observed. The present findings indicate that dietary methylmercury is not a significant source of mercury exposure and is not likely to confound the association of dental amalgam mercury with potential health effects in the present study.